Financial Intelligence - Karen Berman (Harvard Business Review Press, 2013)
Inc. magazine calls it one of “the best, clearest guides to the numbers” on the market. Readers agree, saying it’s exactly “what I need to know” and calling it a “must-read” for decision makers without expertise in finance.